Experiments with the tiny nanosecond output device on the S-300 high-current generator - Kingsep, A.S.; Bakshaev, Yu.L.; Bartov, A.V.; Blinov, P.I.; Chernenko, A.S.; Chikin, R.V.; Chukbar, K.V.; Danko, S.A.; Dubas, L.G.; Kalinin, Yu.G.; Kovalenko, I.V.; Lobanov, A.I.; et al. (Вопросы атомной науки и техники, 2003)
On the S-300 pulsed power generator (4.5 MA, 70 ns, 0.15 Ohm), within the frames of ICF program based on fast high-current Z-pinches, experiments are being carried out studying promising schemes of output units. In particular, a device similar to the plasma flow switch is being investigated aimed at sharpening the pulse. In the experiments with such a device, by means of variation the geometry of the inner electrode of a co-axial, as well as the acceleration of a cascade of plasma “washers”, the switching of the current up to 750 kA has been obtained, with the rise time ~ 5…7 ns and subsequent decrease being in accordance with that of the net current (~ 100 ns). Thereby the opportunity of switching of much more amount of energy onto the load has been demonstrated compared to our preliminary experiments (2.5 MA/2.5 ns). Soft X-ray radiation from the cavity was recorded by means of vacuum diodes with a nickel cathode and especially selected filters. The radiative temperature of the cavity walls estimated from the ratio of diode signals was close to 50 eV.